Learning motivation among international students: the role of demographic factors - Tsai-Fu Chuang; Mei-Hui Lin; Tsaur-Chin Wu; Ming-Da Chuang (BMC Psychology)
Abstract This study examined learning motivation among international students in Taiwan, particularly with respect to differences across various demographic variables and the relationships among these factors, including the ability of some factors to serve as predictors. A total of 260 questionnaires were collected, 210 of which represented valid responses, for an effective sample recovery rate of 80.77%. The process of data analysis included descriptive statistics, t tests, a one-way analysis of variance, correlation analysis, and stepwise multiple regression. The results revealed that students exhibited high levels of intrinsic goal orientation, extrinsic motivation, and task value but only moderate levels of learning beliefs and self-efficacy as well as low levels of emotions, test anxiety, and overall motivation. Significant differences were observed in students’ learning beliefs across different genders and academic disciplines, and significant differences in self-efficacy, test anxiety, and overall motivation were observed across students from different academic years. Gender and academic year were significantly correlated with overall motivation, self-efficacy and learning beliefs, and both characteristics were significant predictors of these factors. These findings highlight the need for targeted interventions aimed at enhancing international students' academic experiences by addressing the complex interactions between demographic factors and learning motivation.